The effects of royal jelly supplementation on anthropometric indices: a GRADE-assessed systematic review and dose-response meta-analysis of randomized controlled trials - Vajdi, Mahdi; Musazadeh, Vali; Khajeh, Mahsa; Safaei, Ehsan; Darzi, Melika; Noshadi, Nooshin; Bazyar, Hadi; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Inconsistent data are available about the effect of royal jelly supplementation on anthropometric indices in humans. This systematic review and meta-analysis was done to summarize data from available randomized controlled trials (RCTs) on the effect of royal jelly supplementation on anthropometric indices such as body weight (BW), body mass index (BMI), and fat mass (FM) in adults. We systematically searched Embase, PubMed, Web of Science, and Scopus databases up to March 2023. All RCTs assessing the effect of royal jelly on anthropometric indices were included. Data were pooled using the random-effects method and were expressed as weighted mean difference (WMD) and 95% confidence intervals (CIs). Sensitivity and subgroup analyses were also performed. Out of 1,492 records, 10 studies that enrolled 512 participants were included. There was no significant effect on BW (WMD: -0.29 kg, 95% CI: -1.24, 0.65, P = 0.543), BMI (WMD: 0.11 kg/m2, 95% CI: -0.29, 0.52, P= 0.583), and FM (WMD: 0.02 %, 95% CI: -0.41, 0.46, P = 0.84). However, we observed a reduction in BW and BMI following royal jelly intake in subgroup of royal jelly dosage < 3000 mg/day. Although the royal jelly supplementation significantly reduced BW and BMI at the dosages < 3000 mg/day, until additional trials have been conducted to assess the effects on obesity measures, it is best to prescribe royal jelly with caution.